Foetal pulmonary maturity in dogs: Estimated from bubble tests in amniotic fluid obtained via amniocentesis. (10th July 2017) - Bonte, T; Del Carro, A; Paquette, J; Charlot Valdieu, A; Buff, S; Rosset, E
Contents: The goal of this study was to evaluate the reliability of amniocentesis during late pregnancy to assess lung maturity in puppies using a bubble test as described by Gunston and Davey (South African Medical Journal, 54, 1978, 495). Thirty‐five bitches from eight different breeds were followed during late pregnancy before undergoing elective Caesarean (C)‐section on days 61–62 after ovulation. Bubble tests were performed the day before the C‐section ( n = 11 bitches) and before the administration of aglepristone on amniotic fluid samples obtained via amniocentesis and were repeated the day of the surgery on amniotic fluid samples collected via puncture of the amniotic bags before they were opened ( n = 35 bitches). No complications were observed following amniocenteses and the C‐sections. The mortality rate (2.3%) was similar to the result of other studies using the same protocol for an elective C‐section. Of the non‐contaminated samples collected the day of the C‐section, 89.6% were positive in the bubble test, which was consistent with observations of clinical maturity the day of the surgery and on the following days. In contrast, 70% of the samples collected the day before the C‐section (when progesterone concentrations were still high) were negative, suggesting that the puppies were still immature at this point in the pregnancy. Additionally, we observed a significant difference in the bubble test results before and 18 hr after the administration of aglepristone, suggesting that aglepristone may act as an inducer of the final maturation of the puppies by inactivating progesterone receptors and simulating a physiological decrease in progesterone. Finally, we confirmed the need to exclude all contaminated samples, which could lead to false‐negative results.